ANALISIS KEPUASAN PELAYANAN KONSUMEN DI PERUSAHAN PELAYANAN PUBLIK MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS DAN ZONE OF TOLERANCE - Firman Hidayat; Devina Puspita Sari; Yugowati Praharsi (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
This company is one of the public service companies in Tuban Regency. In the past 2 (two) years there has been a decline in company transactions. There has been no evaluation regarding the influence of consumer satisfaction on company transactions. This research aims to determine the causal relationship between service quality and consumer satisfaction with sales transactions. This research uses data obtained from consumer satisfaction questionnaires which were randomly distributed to 96 consumers. This research uses the Importance Performance Analysis (IPA) and Zone Of Tolerance (ZOT) methods with the help of the SPSS 26. The results show that from the 25 attributes of the questionnaire statements, there are 21 attributes with negative values on the Service Quality radar diagram, there are 5 attributes that is in Quadrant 1 of the Cartesian Importance Performance Analysis Diagram, and 5 attributes are outside the Zone Of Tolerance. 5 attributes that are outside the Zone of Tolerance become priorities for improving company services and are given recommendations. Companies need to improve services regarding: monitoring of HSE SOPs, competency of service officers, reliability of scheduling systems, and integrated information systems to improve the quality of company services as consumer expected.